A hybrid Monte Carlo study of bond-stretching electron–phonon interactions and charge order in BaBiO3 - Benjamin Cohen-Stead; Kipton Barros; Richard Scalettar; Steven Johnston (npj Computational Materials, 2023)
Abstract The relationship between electron–phonon (e-ph) interactions and charge-density-wave (CDW) order in the bismuthate family of high-temperature superconductors remains unresolved. We address this question using nonperturbative hybrid Monte Carlo calculations for the parent compound BaBiO3. Our model includes the Bi 6s and O 2p σ orbitals and coupling to the Bi-O bond-stretching branch of optical phonons via modulations of the Bi-O hopping integral. We simulate three-dimensional clusters of up to 4000 orbitals, with input model parameters taken from ab initio electronic structure calculations and a phonon energy ℏΩ0 = 60 meV. Our results demonstrate that the coupling to the bond-stretching modes is sufficient to reproduce the CDW transition in this system, despite a relatively small dimensionless coupling. We also find that the transition deviates from the weak-coupling Peierls’ picture. This work demonstrates that off-diagonal e-ph interactions in orbital space are vital in establishing the bismuthate phase diagram.